Anxiety in Higher Education: A Comprehensive Review - , Vishalakshi Choubey, Hem Prakash Verma, Chayanika Hajong, Aparna Purohit (Archives of Current Research International, 2024)
Anxiety, characterized by feelings of unease, worry, and fear, is a prevalent mental health condition among college students. Higher education institutions are facing a growing mental health crisis among their students. Recent studies have shown that mental health issues are increasingly prevalent in this population, with rates of anxiety, depression, and suicidal ideation on the rise. This review paper aims to explore the multifaceted nature of anxiety among college students. To address the mental health crisis in higher education, institutions must take a comprehensive approach that includes prevention, early intervention, and treatment. This may involve providing mental health training for faculty and staff, increasing access to mental health services and promoting mental health awareness and stigma reduction on campus. Additionally, it is important to create a supportive campus environment that fosters student well-being and resilience. Addressing anxiety in higher education is a complex but necessary endeavor. Understanding anxiety factors and interventions' effectiveness can help institutions develop targeted strategies for student mental health support. By prioritizing mental health, institutions can create a more supportive and inclusive campus environment, empowering students to thrive academically and personally.